Morphological and Morphometric Changes of the Gastric Mucosa in Rats Under Combined Pharmacological Exposure - Norbekovich, Toshmamatov Bakhtiyor; Eshmamatovna, Djumanova Nargiza; Dilshodovna, Saifiyeva Kamola (American Journal of Biomedicine and Pharmacy, 2026)
This study focuses on the morphological and morphometric changes of the gastric mucosa in laboratory rats under combined pharmacological exposure. Polypharmacy, or the simultaneous use of multiple drugs, is increasingly common in clinical practice and may significantly affect the structural integrity of the gastrointestinal system. The objective of this research was to evaluate the impact of combined drug administration on the gastric mucosa using experimental rat models. Adult rats were exposed to a combination of pharmacological agents over a defined period, after which gastric tissue samples were collected and analyzed using histological and morphometric methods. The results demonstrated notable alterations in the gastric mucosa, including changes in epithelial thickness, glandular structure distortion, mucosal erosion, and increased inflammatory infiltration. Morphometric analysis revealed statistically significant deviations in key parameters compared to the control group. In conclusion, combined pharmacological exposure induces pronounced morphological and morphometric changes in the gastric mucosa of rats. These findings highlight the potential risk of polypharmacy-related gastrointestinal damage and emphasize the importance of cautious drug administration.